2014
DOI: 10.1037/a0036363
|View full text |Cite
|
Sign up to set email alerts
|

Members’ needs, intragroup conflict, and group performance.

Abstract: Focusing on "what people want in their group" as a critical antecedent of intragroup conflict, the present study theorizes and empirically investigates the relationships among the psychological needs of group members, intragroup conflict, and group performance. It attends to the within-group average and dispersion of members' psychological needs and examines the effects stemming from group composition of needs on multiple types of conflict. The analyses based on multisource data from 145 organizational teams r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 80 publications
0
58
0
Order By: Relevance
“…Bliese's (1998) estimation of ICC values revealed that ICC(2) values higher than .70 were hardly found in groups of fewer than 10 members. For this reason, a number of unit-level studies have reported ICC(2) values lower than .70 (e.g., Cerne, Nerstad, Dysvik, & Skerlavaj, 2014;Chun & Choi, 2014;Ehrhart, 2004;Kirkman, Chen, Farh, Chen, & Lowe, 2009;Wu, Tsui, & Kinicki, 2010). Although scholars maintain that high withinteam agreement (r wg(j) > .70) and between-team variability (significant F-statistics) can justify low ICC(2) values (Bliese, 1998(Bliese, , 2000Kirkman et al, 2009;Wu et al, 2010), future research may need to collect data from larger teams to obtain more reliable measures of team-level constructs and accurately capture team-level phenomena.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Bliese's (1998) estimation of ICC values revealed that ICC(2) values higher than .70 were hardly found in groups of fewer than 10 members. For this reason, a number of unit-level studies have reported ICC(2) values lower than .70 (e.g., Cerne, Nerstad, Dysvik, & Skerlavaj, 2014;Chun & Choi, 2014;Ehrhart, 2004;Kirkman, Chen, Farh, Chen, & Lowe, 2009;Wu, Tsui, & Kinicki, 2010). Although scholars maintain that high withinteam agreement (r wg(j) > .70) and between-team variability (significant F-statistics) can justify low ICC(2) values (Bliese, 1998(Bliese, , 2000Kirkman et al, 2009;Wu et al, 2010), future research may need to collect data from larger teams to obtain more reliable measures of team-level constructs and accurately capture team-level phenomena.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Although conflict mostly occurs during an interpersonal interaction within a team, members experiencing conflict can influence the behaviors of other team members through emotional contagion, which refers to the process of team members subconsciously adapting the emotions of one another (Emich, ). Conflict is widely deemed as a collective phenomenon (Chun & Choi, ; Jehn, ; Jehn & Chatman, ; Peterson & Behfar, ; Simons & Peterson, ). Thus, conflict can be treated as a group‐level variable and refers to the level of disagreement among group members (De Wit et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although conflict mostly occurs during an interpersonal interaction within a team, members experiencing conflict can influence the behaviors of other team members through emotional contagion, which refers to the process of team members subconsciously adapting the emotions of one another (Emich, 2014). Conflict is widely deemed as a collective phenomenon (Chun & Choi, 2014;Jehn, 1995;Jehn & Chatman, 2000;Peterson & Behfar, 2003;Simons & Bonding ties create the opportunity to act together (Adler & Kwon, 2002) and assume the opportunity exists to make the exchange and to produce information benefits (Nahapiet & Ghoshal, 1998). Thus, opportunity is the key to create structural social capital.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…position promotion, increased salary, etc.). Research indicates that individuals with a high need for achievement tend to be creative, generating a large number of solutions to a given problem (Chun and Choi, 2014). This proactive competition could arouse team members' work initiatives and creativity and thus improve team innovation performance.…”
Section: H2amentioning
confidence: 99%